The Evolution of the Arab Cold War (Journal of Human Sciences, 2024)
The Arab cold war, in the aftermath of Arab uprising, seems to bear a resemblance to  important similarities with the fifties and sixties conflicts in the area which Malcolm Kerr called “the Arab cold war.” The power of the major protagonists in the Arab cold war was measured in their ability to affect  political struggles in neighboring states where weak regimes had trouble controlling their own societies and local players sought regional allies against their own domestic opponents. Non-state actors played major roles. One aspect of the new Arab cold war is the paradox of power, where a state’s own military power is not used as a war tool. Instead, the key is to be able to support non-state actors effectively in their domestic political battles within the weak states of the Arab world. The complicated and violent regional politics of the Arab world or the Middle East is better understood as a cold war among a number of regional players, both states and non- state actors, in which Iran and Saudi Arabia play the leading roles. It is a cold war because these two main actors are not confronting and most probably will not confront each other militarily. Rather, their contest for influence plays out in the domestic political systems of the region’s weak states. Non-Arab players have joined the race for leadership and influence. Iran has become a major protagonist in the new Middle East cold war. Turkey has made a bid for a greater regional role. It is not an ideological battle of “progressives” versus “reactionaries.” The line-ups are less ideological and more identity-based. Non-state actors played major roles.